Dr. Lisa yoga blast [videorecording (DVD)] - Schultz, Ernie; Schultz, Ernie (Acacia : Distributed by Acorn Media U.S., 2012)
Dr. Lisa Masterson, from the TV series The doctors, and her trainer Elise Joan demonstrate three 20-minute low-impact yoga workouts for burning calories, reducing fat, building strength, and increasing flexibility.